The Renaissance in Rome - Stinger, Charles L., 1944- (Bloomington : Indianapolis : Indiana University Press, 1998)
Probes the basic attitudes, the underlying values and the core convictions that Rome's intellectuals and artists experienced, lived for, and believed in from Pope Eugenius IV's reign to the Eternal City in 1443 to the sacking of 1527.
Includes bibliographical references (p. [401]-427) and index.
Keywords: Renaissance -- Italy -- Rome; Rome (Italy) -- Civilization -- 15th century; Rome (Italy) -- Civilization -- 16th century; Papacy -- History -- 1447-1565.; Geschichte 1420-1600.; Renaissance; Rom